A kind of high thermal conductivity and high microwave absorption aluminum nitride ceramic material and preparation method thereof
By introducing excessive carbon and rare earth metal oxide doping in γ-Al2O3, aluminium nitride ceramic with high thermal conductivity and high microwave absorption was prepared, which solved the problem of insufficient dielectric loss of AlN ceramics and achieved high thermal conductivity and microwave absorption performance The improvement is suitable for high-power microwave electronic vacuum devices and reduces production costs.
Patent Information
- Application Number
- CN202311407268.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-10-26
AI Technical Summary
AlN ceramics are difficult to meet the requirements of high thermal conductivity and microwave absorption performance in high-power microwave electronic vacuum devices applications due to too low dielectric loss. The prior art introduces second phase doping with high microwave absorption performance directly into AlN. Limited.
Excess carbon is introduced into γ-Al2O3, and submicron AlN powder is prepared by carbon-thermal reduction and nitriding method. It is doped with rare earth metal oxides and alkaline earth metal compounds, and is prepared by dry press molding and hot press sintering. Aluminum nitride ceramics with thermal conductivity and high microwave absorption.
It achieves high thermal conductivity, excellent microwave absorption and mechanical properties, reduces sintering temperature, is suitable for high-power microwave electronic vacuum devices, and has low process cost and is suitable for mass production.
Smart Images

Figure CN117510212B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an aluminum nitride (AlN) ceramic material with high thermal conductivity and high microwave absorption and a preparation method thereof, and belongs to the field of dielectric ceramics. Background Art
[0002] High-power microwave electronic vacuum devices require microwave absorbing materials to have both excellent high thermal conductivity and microwave absorption properties.
[0003] AlN ceramics have excellent properties such as high thermal conductivity, high dielectric strength, low dielectric constant, high mechanical strength, chemical stability and non-toxicity. However, due to its low dielectric loss (10 -4 There is still a long way to go before the practical application of high-power microwave electronic vacuum devices.
[0004] Since AlN is a covalent compound and is difficult to react chemically with other substances, a second phase with high microwave absorption performance is usually used to adjust the microwave absorption performance of AlN ceramics. Specifically, a certain amount of a conductor, semiconductor or dielectric second phase with high microwave absorption is added to AlN powder, such as tungsten, copper, graphite, glassy carbon, carbon nanotubes, silicon carbide, etc., and high thermal conductivity microwave absorption aluminum nitride ceramics can be prepared through mixing, molding and sintering. Summary of the invention
[0005] In view of the above research status, the present invention innovatively introduces excessive carbon (C, carbon black, graphite, glassy carbon, carbon nanotubes, etc.) into γ-Al2O3 through carbothermal reduction and nitridation (CTRN) to first prepare submicron AlN powder containing C, and then combine it with a small amount of rare earth metal oxides and alkaline earth metal compounds for doping, dry pressing, hot pressing and sintering, and finally obtain high thermal conductivity microwave absorbing aluminum nitride ceramics.
[0006] The present invention provides a high thermal conductivity and high microwave absorption aluminum nitride ceramic material and a preparation method thereof, comprising:
[0007] (1) mixing carbon-containing submicron AlN powder, rare earth metal oxide and alkaline earth metal compound to obtain a mixed powder;
[0008] (2) The obtained mixed powder is pressed into a shape and then hot-pressed and sintered to obtain an aluminum nitride ceramic material with high thermal conductivity and high microwave absorption.
[0009] In this field, a second phase with high microwave absorption performance is usually directly added to AlN powder, and the microwave absorption performance of the ceramic is adjusted through molding and sintering processes. The present invention adopts γ-Al2O3 and C to mix in a specific ratio (ensuring excessive C), and prepares a powder containing both submicron AlN and nanometer C through the CTRN process, and then mixes with rare earth metal oxides and alkaline earth metal compound sintering aids, and obtains high thermal conductivity microwave absorption aluminum nitride ceramics through dry pressing molding and hot pressing sintering. Excessive amorphous C is introduced into γ-Al2O3. On the one hand, C is used as a reaction raw material to prepare submicron AlN powder using CTRN, ensuring that γ-Al2O3 is fully converted into AlN; on the other hand, excess C is used as a microwave absorber to improve the microwave absorption performance of AlN ceramics; in addition, excess C is uniformly mixed with submicron AlN in the form of nanoparticles, which increases the bulk density of the green blank and reduces the sintering temperature. Rare earth metal oxides and alkaline earth metal compounds react with the impurity oxygen (aluminum oxide) in AlN to generate an appropriate amount of low-temperature liquid phase, which can achieve dense sintering of AlN ceramics under low temperature conditions, promote the grain growth of aluminum nitride ceramics, and maintain the high thermal conductivity of AlN ceramics.
[0010] Preferably, the molar content of C in the C-containing submicron AlN powder is 10 to 31 mol %; and the particle size of the carbon-containing submicron AlN powder is 500 to 1500 nm.
[0011] Preferably, the method for preparing the carbon-containing submicron AlN powder comprises: preparing and mixing the ingredients according to a molar ratio of γ-Al2O3:carbon material of 1:3.2-3.6, and then subjecting the ingredients to carbon thermal reduction nitridation to obtain carbon-containing submicron AlN ceramic powder; the parameters of the carbon thermal reduction nitridation method include: a nitrogen atmosphere of 0.005-0.05MPa, a temperature of 1500-1800°C, and a time of 2-10 hours.
[0012] Preferably, the γ-Al2O3 is a high-purity nanopowder with a purity of ≥99.9% and a particle size of ≤100nm;
[0013] The carbon material is high-purity nano-carbon powder. Preferably, the carbon material is selected from at least one of carbon black, graphite, glassy carbon, and carbon nanotubes, with a purity of ≥99.9% and a particle size of ≤100nm.
[0014] Preferably, the rare earth metal oxide is selected from at least one of La2O3, Y2O3, Gd2O3, Yb2O3 and Sc2O3; and the added amount of the rare earth metal oxide is 2 to 10 wt% of the carbon-containing submicron AlN powder.
[0015] Preferably, the alkaline earth metal compound is selected from at least one of alkaline earth metal oxides, alkaline earth metal carbonates or alkaline earth metal fluorides, preferably at least one of MgO, CaO, SrO, BaO, MgCO3, CaCO3, SrCO3, BaCO3, MgF2, CaF2, BaF2; the addition amount of the alkaline earth metal compound is 100-500ppm of the carbon-containing submicron AlN powder.
[0016] Preferably, the pressing method is dry pressing; the pressure of the dry pressing is 2 to 20 MPa, and the holding time is 30 to 300 seconds; the parameters of the hot pressing sintering include: the atmosphere is a flowing nitrogen atmosphere, the pressure is 5 to 50 MPa, the temperature is 1700 to 1900°C, and the sintering time is 2 to 10 hours; the pressure of the flowing nitrogen atmosphere is 0.005 to 0.05 MPa, preferably 0.003 MPa, and the flow rate is 0.5 to 2 L / min, preferably 1.0 L / min.
[0017] The present invention also provides a high thermal conductivity, high microwave absorption aluminum nitride ceramic material obtained according to the above-mentioned preparation method, wherein the physical phases of the high thermal conductivity, high microwave absorption aluminum nitride ceramic material are wurtzite-type aluminum nitride phase, garnet phase, and amorphous carbon, and the relative density is ≥99.5%.
[0018] Preferably, the grain size of the aluminum nitride ceramic material with high thermal conductivity and high microwave absorption is 3-10 μm, the garnet phase is distributed at the grain boundaries, and the nanoparticles of amorphous C are gathered inside the aluminum nitride grains and at the grain boundaries.
[0019] Preferably, the thermal conductivity of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material at room temperature is ≥50 W / m·K;
[0020] The dielectric constant of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material between 2 and 18 GHz is ≥10, and the dielectric loss between 2 and 18 GHz is ≥0.2;
[0021] The bending strength of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material is ≥350MPa;
[0022] The hardness of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material is ≥8GPa;
[0023] The fracture toughness of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material is ≥3MPa·m 1 / 2 ;
[0024] The thermal expansion coefficient of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material is 4.0 to 5.5 ppm / ℃ between.
[0025] Beneficial effects of the present invention:
[0026] (1) Different from directly introducing a second phase with high microwave absorption performance into AlN, the present invention innovatively introduces excess amorphous C into the raw material powder (γ-Al2O3). On the one hand, C is used as a reaction raw material to produce submicron AlN powder using CTRN to ensure that γ-Al2O3 is fully converted into AlN; on the other hand, the excess C acts as a microwave absorber to improve the microwave absorption performance of AlN ceramics; in addition, the excess C is uniformly mixed with submicron AlN in the form of nanoparticles to increase the packing density of the green body and reduce the sintering temperature. Combined with the doping of rare earth metal oxides and alkaline earth metal compounds, high thermal conductivity microwave absorption aluminum nitride ceramics are prepared.
[0027] (2) The C-containing submicron AlN powder material provided by the present invention has a ceramic material prepared by hot pressing and sintering, which has high thermal conductivity, good microwave absorption performance and excellent mechanical properties.
[0028] (3) The present invention uses γ-Al2O3 and nano-C, which are in sufficient supply in the domestic market, cheaper and easier to localize, making it possible to prepare high-performance ceramics at a low cost.
[0029] (4) The material described in the present invention is mainly mixed by a planetary ball mill, and the ceramic is sintered by hot pressing. The ceramic material has stable performance and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a SEM image of the C-containing AlN powder prepared in Example 1;
[0031] Figure 2 The XRD diffraction pattern of the C-containing AlN ceramic prepared in Example 1;
[0032] Figure 3 This is the SEM cross-sectional morphology of the AlN ceramic prepared in Example 1;
[0033] Figure 4 This is a diagram of the dielectric properties of the high thermal conductivity microwave absorbing aluminum nitride ceramic prepared in Example 1 at a frequency of 2-18 GHz, where (a) is the dielectric constant and (b) is the dielectric loss. DETAILED DESCRIPTION
[0034] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0035] The present invention prepares C-containing submicron AlN powder by doping γ-Al2O3 with excessive C through the CTRN process, and combines rare earth metal oxides and alkaline earth metal compounds to prepare high thermal conductivity microwave absorbing aluminum nitride ceramic materials. Different from the existing reports of doping AlN with a second phase with high microwave absorption performance, the present invention introduces excessive C into γ-Al2O3. On the one hand, C is used as a reaction raw material to prepare submicron AlN powder using CTRN to ensure that γ-Al2O3 is fully converted into AlN; on the other hand, excessive C is used as a microwave absorber to improve the microwave absorption performance of AlN ceramics; in addition, excessive C is uniformly mixed with submicron AlN in the form of nanoparticles, thereby increasing the bulk density of the green blank and reducing the sintering temperature. Rare earth metal oxides and alkaline earth metal compounds react with impurity oxygen (aluminum oxide) in AlN as sintering aids to generate an appropriate amount of low-temperature liquid phase, which can realize the dense sintering of AlN ceramics under low temperature conditions, promote the growth of aluminum nitride ceramic grains, and improve the thermal conductivity of AlN ceramics.
[0036] The following is an exemplary description of the preparation method of the high thermal conductivity microwave absorbing aluminum nitride ceramic material of the present invention. The preparation method mainly includes two parts: preparation of submicron AlN powder containing C and preparation of high thermal conductivity microwave absorbing aluminum nitride ceramic.
[0037] Batching. Batching is carried out according to the molar ratio of γ-Al2O3:C of 1:(3.2-3.9) (preferably 1:(3.3-3.6)) to obtain a powder. Wherein, the γ-Al2O3 is a high-purity nano powder with a purity of ≥99.9% and a particle size of ≤100nm; the C is a high-purity nano powder with a purity of ≥99.9% and a particle size of ≤100nm. Too much C content will make it difficult to sinter the ceramic to a dense state, which will lead to a decrease in mechanical properties, a significant decrease in thermal conductivity, and a significant decrease in dielectric constant. If the C content is too low, the aluminum oxide is not fully converted into aluminum nitride, resulting in low thermal conductivity of the ceramic, and there is not enough C to absorb microwaves, resulting in a significant decrease in the microwave absorption performance of the ceramic.
[0038] Mix the powder, deionized water and high-purity alumina balls in a mass ratio of 1:1:5, and ball-mill for 12 to 30 hours at 250 to 300 rpm to obtain a uniformly mixed ball-milled material.
[0039] Drying and sieving: Dry the ball mill material at 60-100°C for 24 hours and sieve it through a 100-150 mesh sieve to obtain a raw material powder.
[0040] Carbon thermal reduction nitridation. The raw material powder is subjected to carbon thermal reduction nitridation treatment at 1500-1800°C for 2-10 hours to prepare a submicron AlN ceramic powder containing C. The container used is a graphite crucible, the nitrogen source is high-purity nitrogen (purity>99.99%), the pressure of the flowing nitrogen atmosphere is about 0.05-0.1MPa, and the nitrogen flow rate is 0.5-2.0L / min; the AlN generated is a high-purity submicron powder with a particle size of 0.5-1.5μm and an oxygen content of ≤1.0wt%; amorphous C is distributed around the AlN particles in the form of nanoparticles.
[0041] Mixing. The rare earth metal oxide, alkaline earth metal compound and AlN powder containing C are ball-milled and mixed, alcohol is selected as the solvent, and the grinding balls are high-purity alumina balls. The ball-milling is carried out at a rotation speed of 250 to 300 rpm for 12 to 24 hours to obtain a mixed slurry. The mixed slurry is dried at 60 to 120° C. for 24 hours and sieved to obtain a mixed powder.
[0042] In an optional embodiment, the rare earth oxide source is selected from at least one of La2O3, Y2O3, Gd2O3, Yb2O3 and Sc2O3, with a purity ≥99.9%; the alkaline earth metal compound source is selected from at least one of MgO, CaO, SrO, BaO, MgCO3, CaCO3, SrCO3, BaCO3, MgF2, CaF2, BaF2, with a purity ≥99.9%.
[0043] In an optional embodiment, the addition amount of the rare earth metal oxide is 2 to 10 wt % of the AlN ceramic powder containing C. Too high or too low will cause the thermal conductivity of the ceramic to decrease. If the rare earth metal oxide content is too low, too little low-temperature liquid phase will be generated, which may cause oxygen to remain in the AlN grains and fail to achieve low-temperature densification sintering, resulting in a decrease in the thermal conductivity of the ceramic; if the rare earth metal oxide content is too high, an unknown second phase with low thermal conductivity may be generated, resulting in a decrease in thermal conductivity. In an optional embodiment, the addition amount of the alkaline earth metal compound is 100 to 500 ppm. If the alkaline earth metal compound content is too low, too little liquid phase will be generated in the ceramic, resulting in too high oxygen content on the surface of the AlN particles, resulting in oxygen defects formed in the AlN lattice, reducing the thermal conductivity of the ceramic; if the alkaline earth metal compound content is too high, it may cause the generation of other alkaline earth metal second phases with low thermal conductivity, which will wrap the AlN ceramic grains and also cause the thermal conductivity of the ceramic to decrease.
[0044] Molding. The obtained mixed powder is dry pressed to obtain a ceramic green body. The dry pressing pressure is 2 to 20 MPa, and the holding time is 30 to 300 seconds.
[0045] Hot pressing and sintering. In a flowing nitrogen atmosphere, the ceramic blank is hot pressed and sintered at 1700-1900°C for 2-10 hours to obtain a high thermal conductivity microwave absorbing aluminum nitride ceramic. Wherein, the pressure of the flowing nitrogen atmosphere is 0.005-0.05MPa, and the flow rate is 0.5-5L / min. In the hot pressing and sintering process, on the basis of the reaction of the sintering aid and alumina to generate a low-temperature liquid phase, an external force is applied to promote the densification sintering of the ceramic under low temperature conditions and improve the thermal conductivity of the ceramic. It should be noted that if the sintering temperature is too low, the density of the ceramic will be low and the pore content will be high, resulting in a decrease in the thermal conductivity of the ceramic; if the temperature is too high, the ceramic phase may change, or part of the low-temperature liquid phase may precipitate too much, reducing the thermal conductivity of the ceramic.
[0046] Different from the conventional method, a second phase with high microwave absorption performance is directly added to AlN powder, and the microwave absorption performance of the ceramic is adjusted through molding and sintering. The present invention adopts γ-Al2O3 and C to mix in a specific ratio (ensuring excessive C), and prepares a powder containing both submicron AlN and nano C through the CTRN process. Excessive C is introduced into γ-Al2O3. On the one hand, C is used as a reaction raw material to prepare submicron AlN powder using CTRN to ensure that γ-Al2O3 is fully converted into AlN; on the other hand, excess C is used as a microwave absorber to improve the microwave absorption performance of AlN ceramics; in addition, excess C is uniformly mixed with submicron AlN in the form of nanoparticles, which increases the bulk density of the blank and reduces the sintering temperature. After adding an appropriate amount of rare earth metal oxides and alkaline earth metal compounds, high thermal conductivity microwave absorption aluminum nitride ceramics are obtained after dry pressing molding and hot pressing sintering. The sintering aid reacts with the impure oxygen (aluminum oxide) in AlN to generate an appropriate amount of low-temperature liquid phase. Combined with hot pressing sintering, it can not only promote the dense sintering of ceramics under low temperature conditions to achieve high thermal conductivity, but also achieve higher microwave absorption performance.
[0047] The phases of the aluminum nitride ceramic material with high thermal conductivity and high microwave absorption prepared by the method provided by the present invention are wurtzite aluminum nitride phase, garnet phase and amorphous carbon. The grain size of the aluminum nitride ceramic is 3 to 10 μm, the garnet phase is distributed at the grain boundary, and the nanoparticles of amorphous C are gathered inside the aluminum nitride grains and at the grain boundary.
[0048] Performance Testing:
[0049] The relative density of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material is ≥99.5%; the thermal conductivity at room temperature is ≥50W / m·K, the dielectric constant is ≥10 (@2-18GHz), and the dielectric loss is ≥0.2 (@2-18GHz); the bending strength of the ceramic material tested by three-point bending is ≥350MPa; the hardness of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material tested by indentation method is ≥8GPa; the fracture toughness is ≥3MPa·m 1 / 2;The coefficient of thermal expansion is between 4.0-5.5ppm / ℃.
[0050] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0051] Example 1
[0052] (1) Ingredients. The ingredients are prepared according to a mass ratio of γ-Al2O3:C of 1:3.3. The particle size of the γ-Al2O3 powder is about 30nm; the particle size of the C powder is about 20nm;
[0053] (2) Mixing. The powder obtained in step (1): deionized water: high-purity alumina balls are mixed in a mass ratio of 1:1:5, and ball-milled at 250 rpm for 20 hours to obtain a uniformly mixed ball-milled material;
[0054] (3) Drying and sieving. The ball mill obtained in step (2) is dried at 60°C for 24 hours and passed through a 100-mesh sieve;
[0055] (4) Carbothermal reduction nitridation: The powder obtained in step (3) is subjected to carbothermal reduction nitridation at 1650°C for 4 hours to prepare a C-containing submicron AlN ceramic powder;
[0056] (5) Mixing. 4.0 g Y2O3 and 200 ppm CaO are added to AlN powder and ball milled. The solvent is alcohol and the grinding balls are high-purity alumina balls. The ball milling is carried out at a speed of 270 rpm for 20 hours to obtain a mixed slurry. The mixed slurry is dried at 60° C. for 24 hours and sieved to obtain a mixed powder.
[0057] (6) Molding. The mixed powder obtained in step (5) is dry-pressed to obtain a ceramic green body;
[0058] (7) Hot pressing and sintering. Under a pressure of 20 MPa, the ceramic blank obtained in step (6) is hot pressed and sintered at 1825° C. for 5 hours in a flowing nitrogen atmosphere at a certain pressure to obtain AlN ceramics. The pressure of the flowing nitrogen atmosphere is 0.02 MPa, and the flow rate is 2 L / min.
[0059] Example 2
[0060] (1) Ingredients. The ingredients are prepared according to a mass ratio of γ-Al2O3:C powder of 1:3.4 to obtain a powder. The particle size of the γ-Al2O3 powder is about 30 nm; the particle size of the carbon powder is about 20 nm;
[0061] (2) Mixing. The powder obtained in step (1): deionized water: high-purity alumina balls are mixed in a mass ratio of 1:1:5, and ball-milled at 270 rpm for 24 hours to obtain a uniformly mixed ball-milled material;
[0062] (3) Drying and sieving. The ball mill obtained in step (2) is dried at 60°C for 24 hours and passed through a 120-mesh sieve;
[0063] (4) Carbothermal reduction nitridation: The powder obtained in step (3) is subjected to carbothermal reduction nitridation at 1600°C for 2 hours to prepare a C-containing submicron AlN ceramic powder;
[0064] (5) Mixing. 4.1 g Y2O3 and 180 ppm CaF2 were added to AlN powder and ball-milled. The solvent was alcohol and the grinding balls were high-purity alumina balls. The mixture was ball-milled at a speed of 270 rpm for 20 hours to obtain a mixed slurry. The mixed slurry was dried at 60° C. for 24 hours and sieved to obtain a mixed powder.
[0065] (6) Molding. The mixed powder obtained in step (5) is dry-pressed to obtain a ceramic green body;
[0066] (7) Hot pressing and sintering. Under a pressure of 15 MPa, the ceramic blank obtained in step (6) is hot pressed and sintered at 1800° C. for 5 hours in a flowing nitrogen atmosphere at a certain pressure to obtain AlN ceramics. The pressure of the flowing nitrogen atmosphere is 0.03 MPa and the flow rate is 1.0 L / min.
[0067] Example 3
[0068] (1) Ingredients. Ingredients are prepared according to a mass ratio of γ-Al2O3:C powder of 1:3.5 to obtain powder. The particle size of the γ-Al2O3 powder is 30 nm; the particle size of the carbon powder is 20 nm;
[0069] (2) Mixing. The powder obtained in step (1): deionized water: high-purity alumina balls are mixed in a mass ratio of 1:1:5, and ball-milled at 270 rpm for 28 hours to obtain a uniformly mixed ball-milled material;
[0070] (3) Drying and sieving. The ball mill obtained in step (2) is dried at 60°C for 24 hours and passed through a 100-mesh sieve;
[0071] (4) Carbothermal reduction nitridation: The powder obtained in step (3) is subjected to carbothermal reduction nitridation at 1600°C for 2 hours to prepare a C-containing submicron AlN ceramic powder;
[0072] (5) Mixing. 4.2 g of Y2O3 and 150 ppm of CaO were added to AlN powder and ball-milled. The solvent was alcohol and the grinding balls were high-purity alumina balls. The mixture was ball-milled at a speed of 270 rpm for 20 hours to obtain a mixed slurry. The mixed slurry was dried at 60° C. for 24 hours and sieved to obtain a mixed powder.
[0073] (6) Molding. The mixed powder obtained in step (7) is dry-pressed to obtain a ceramic green body;
[0074] (7) Hot pressing and sintering. Under a pressure of 25 MPa, the ceramic blank obtained in step (6) is hot pressed and sintered at 1750° C. for 5 hours in a flowing nitrogen atmosphere at a certain pressure to obtain AlN ceramics. The pressure of the flowing nitrogen atmosphere is 0.01 MPa and the flow rate is 1.0 L / min.
[0075] Example 4
[0076] The preparation process of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material in Example 4 is similar to that in Example 1, with the only difference being that the molar ratio of γ-Al2O3 to C is 1:3.401.
[0077] Example 5
[0078] The preparation process of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material in Example 5 is similar to that in Example 1, with the only difference being that the molar ratio of γ-Al2O3 to C is 1:3.554.
[0079] Example 6
[0080] The preparation process of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material in Example 6 is similar to that in Example 1, with the only difference being that the molar ratio of γ-Al2O3 to C is 1:3.800.
[0081] Example 7
[0082] The preparation process of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material in Example 7 is similar to that in Example 1, with the only difference being that the molar ratio of γ-Al2O3 to C is 1:3.900.
[0083] Comparative Example 1
[0084] The preparation process of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material in Comparative Example 1 refers to that in Example 1, with the only difference being that the molar ratio of γ-Al2O3 to C is 1:3.000.
[0085] Comparative Example 2
[0086] The preparation process of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material in Comparative Example 2 refers to that in Example 1, with the only difference being that the molar ratio of γ-Al2O3 to C is 1:4.000.
[0087] Table 1 shows the mass ratios of various raw materials and main sintering process parameters used in Examples 1-3:
[0088]
[0089] Table 2 shows the main performance parameters of the high thermal conductivity microwave absorbing aluminum nitride ceramics obtained in Examples 1-3:
[0090]
[0091] As can be seen from Table 2, the phases of the high thermal conductivity microwave absorbing aluminum nitride ceramic obtained by doping aluminum nitride ceramic powder containing C with rare earth metal oxides and alkaline earth metal compounds and hot pressing and sintering are wurtzite aluminum nitride phase, garnet phase, and amorphous carbon, and the relative density is ≥99.5%; the thermal conductivity of the aluminum nitride ceramic sample at room temperature is ≥50W / m·K, Figure 4 It can be seen that the dielectric constant of the high thermal conductivity microwave absorbing aluminum nitride ceramic at a frequency of 2-18 GHz is ≥10, and the dielectric loss is ≥0.2.
[0092] Table 3 shows the main performance parameters of the high thermal conductivity microwave absorbing aluminum nitride ceramics obtained in Examples 1-3
[0093]
[0094] As can be seen from Table 3, the high thermal conductivity microwave absorbing aluminum nitride ceramics obtained by doping C-containing submicron aluminum nitride ceramic powders with rare earth metal oxides and alkaline earth metal compounds through hot pressing and sintering have a bending strength of ≥350MPa, a hardness of ≥8GPa, and a fracture toughness of ≥3MPa·m at room temperature. 1 / 2 , thermal expansion coefficient is 4.0~5.5ppm / ℃ between.
[0095] Figure 1 This is the SEM image of the C-containing AlN powder prepared in Example 1. It can be seen from the figure that C is evenly distributed around the AlN grains in the form of nanoparticles. The AlN grain size D 50 =0.75±0.01μm;
[0096] Figure 2 The XRD diffraction pattern of AlN ceramic containing C prepared in Example 1 is composed of AlN, YAG (Y3Al5O 12), amorphous C, and the corresponding standard cards are AlN (PDF#75-1620), Y3Al5O 12 (PDF#09-0310). At the same time, no other phases were found;
[0097] Figure 3 This is the SEM cross-sectional morphology of the AlN ceramic prepared in Example 1. It can be seen from the figure that the overall morphology of the AlN ceramic is dense, and the grain size of the AlN ceramic is about 5μm. Among them, YAG is distributed at the grain boundaries in the form of a second phase, and C is distributed at both the grain boundaries and the grains, and still exists in the form of nano C particles.
[0098] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A method for preparing a high thermal conductivity and high microwave absorption aluminum nitride ceramic material, characterized in that: include: (1) preparing and mixing the ingredients according to a molar ratio of γ-Al2O3:carbon material of 1:(3.2-3.9), and then subjecting the mixture to a carbon thermal reduction nitridation method to obtain a carbon-containing submicron AlN ceramic powder; The parameters of the carbon thermal reduction nitridation method include: nitrogen atmosphere of 0.005-0.05 MPa, temperature of 1500-1800° C., and time of 2-10 hours; The molar content of carbon in the carbon-containing submicron AlN powder is 10 to 31 mol%; the carbon-containing submicron AlN powder, rare earth metal oxide and alkaline earth metal compound are mixed to obtain a mixed powder; the rare earth metal oxide is added in an amount of 2 to 10 wt% of the carbon-containing submicron AlN powder; the alkaline earth metal compound is added in an amount of 100 to 500 ppm of the carbon-containing submicron AlN powder; (2) The obtained mixed powder is pressed into a shape and then hot-pressed and sintered to obtain a high thermal conductivity and high microwave absorption aluminum nitride ceramic material.
2. The preparation method according to claim 1, characterized in that: The particle size of the carbon-containing submicron AlN powder is 500-1500nm.
3. The preparation method according to claim 1, characterized in that: The γ-Al2O3 is a high-purity nano powder with a purity of ≥99.9% and a particle size of ≤100nm; The carbon material is high-purity nano-carbon powder with a purity of ≥99.9% and a particle size of ≤100nm.
4. The preparation method according to claim 3, characterized in that: The carbon material is selected from at least one of carbon black, graphite, glassy carbon and carbon nanotubes.
5. The preparation method according to claim 1, characterized in that: The rare earth metal oxide is selected from at least one of La2O3, Y2O3, Gd2O3, Yb2O3 and Sc2O3.
6. The preparation method according to claim 1, characterized in that: The alkaline earth metal compound is selected from at least one of alkaline earth metal oxides, alkaline earth metal carbonates or alkaline earth metal fluorides.
7. The preparation method according to claim 6, characterized in that: The alkaline earth metal compound is selected from at least one of MgO, CaO, SrO, BaO, MgCO3, CaCO3, SrCO3, BaCO3, MgF2, CaF2, and BaF2.
8. The preparation method according to claim 1, characterized in that: The pressing method is dry pressing; the pressure of the dry pressing is 2-20 MPa, and the holding time is 30-300 seconds; The parameters of the hot pressing sintering include: the atmosphere is a flowing nitrogen atmosphere, the pressure is 5-50MPa, the temperature is 1700-1900°C, and the sintering time is 2-10 hours; the pressure of the flowing nitrogen atmosphere is 0.005-0.05MPa, and the flow rate is 0.5-2L / min.
9. A high thermal conductivity and high microwave absorption aluminum nitride ceramic material obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The physical phases of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material are wurtzite aluminum nitride phase, garnet phase and amorphous carbon, and the relative density is ≥99.5%.
10. The high thermal conductivity and high microwave absorption aluminum nitride ceramic material according to claim 9, characterized in that: The grain size of the aluminum nitride ceramic material with high thermal conductivity and high microwave absorption is 3-10 μm, the garnet phase is distributed at the grain boundaries, and the nanometer particles of amorphous C are gathered inside the aluminum nitride grains and at the grain boundaries.
11. The high thermal conductivity and high microwave absorption aluminum nitride ceramic material according to claim 9, characterized in that: The thermal conductivity of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material at room temperature is ≥50W / m·K; The dielectric constant of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material between 2 and 18 GHz is ≥10, and the dielectric loss between 2 and 18 GHz is ≥0.2; The bending strength of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material is ≥350MPa; The hardness of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material is ≥8GPa; The fracture toughness of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material is ≥3MPa·m 1 / 2 ; The thermal expansion coefficient of the high thermal conductivity and high microwave absorption aluminum nitride ceramic material is 4.0 to 5.5 ppm / o Between C.
